Review article: A primer for clinical researchers in the emergency department: Part VIII. Implementation science: An introduction. (24th April 2019) - Tavender, Emma; Babl, Franz E; Middleton, Sandy
Abstract: New research findings may not lead to change in practice, or a change at the front line may be delayed by years. A number of terms have been used to describe efforts and strategies to speed a change in evidence‐based practice, such as: implementation science, knowledge translation, research translation and others. In contrast to traditional clinical research, implementation science generally aims to understand and change health professional behaviour to promote evidence uptake as opposed to attempting to change patient behaviour. There are now theoretical frameworks and evolving evidence providing guidance how to change clinician behaviour and, specifically, emerging evidence on how to achieve this in the emergency setting. This review will provide an introduction to implementation science and illustrate how to target evidence practice gaps using ED examples.